PATRIARCHY SYSTEM PORTRAYED IN THE SHIRLEY JACKSON'S THE LOTTERY SHORT STORY - KINANTI, SAYEKTI PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Feminism, Patriarchy System, EffortIn a patriarchal society, women are considered subordinate to men because of their position in the family and the society. Patriarchy system explains that family is the primary source where the doctrine of patriarchy is applied. This patriarchal system also describes that family, society, and state have relations interrelated to regulate its citizens through the head of family. The patriarchy system toward women characters is the major issues in Shirley Jackson The Lottery. Therefore, the writer conducts this thesis in order to reveal the patriarchy system faced by women characters of the short story and also the way the main character efforts against the patriarchy system.The writer sees the patriarchy system and the efforts by the main characters through feminist point of view. The writer’s analysis finds that all of women characters face patriarchy system in their environment. They have different behavior with men and also as men’s property in marriage. They also have to deal with strictness toward wives and children who treat them really weak. To make it worst, the society also discriminates them merely because they are women.In the other hand, Tessie Hutchinson is the only main women character who shows awareness of the role of women in resistance. Although she has faced oppressions and subordination, Tessie has her own way to survive and endure all the pain and suffering. Tessie’s effort is a natural reaction of her oppressed condition and for her own survival. Her ways of effort against subordinations and oppressions in patriarchy system are shown by her late arrival to the lottery and her protest when she gets the lottery. However, her effort fails, it is because there is no people who support her efforts against the patriarchal system. The people more adhere to the rules that have been applied in the patriarchal society. They are afraid to violate the rules because of tradition.